Navigating ethics: social media challenges in Indonesian dental practice - Sarwono, Aditya Pratama; Louisa, Marie (International Journal of Public Health Science (IJPHS), 2025)
Social media has evolved into an important tool for dental practitioners to promote their services and attract patients, necessitating a careful balance between effective promotion and upholding ethical standards to maintain patient trust. This research delves into the challenges and implications associated with using social media in dentistry, emphasizing the ethical considerations, legal frameworks, and the potential impact on public understanding of oral and dental health. By providing a comprehensive discussion on the importance of ethical promotion in the dental profession, the study not only highlights the need for dental practitioners to prioritize ethical standards in their social media activities but also offers effective strategies for attracting patients. These strategies include delivering relevant and informative content, engaging with followers, demonstrating professionalism and expertise, obtaining informed consent, and respecting patient privacy. The research underscores that navigating these complexities is essential for dental practitioners to promote their services ethically, contributing to the success and growth of their practice while safeguarding the integrity of health information and fostering positive relationships with the public.